An empirical investigation of IT innovation implementation in higher education institutions in Indonesia - Huda, Muhammad Qomarul (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2017)
The IT innovation implementation in Higher Education Institutions (HEIs) is commonly considered to be one of the key drivers of organizational success. Many empirical studies showed that implementing IT innovation improves organizational productivity, which in turn will enhance organizational performance. While many past studies on IT innovation focused on the industrial sector, research that examined IT innovation in the context of HEI were emerging. Among these researches, it was found that not many focused on post-adoption behaviour of IT innovation and it appeared that there was still some disagreement among the information system (IS) researchers and practitioners on the issue. Review of past literature also indicated that the level of IT implementation success was rather low. Many organizations when they proceeded to the IT implementation stage, they faced many problems. The actual problem was not IT adoption failure, but rather IT implementation failure. The organization failed to get their employees to be committed and consistent in using IT innovation that they adopted. In some cases, they did not get the benefits as expected. Additionally, it was also found that studies conducted on IT innovation in HEI of the developing countries were scarce. Since the characteristics of HEIs in developing countries may be different than their counterparts of the Developed nations, it is therefore imperative for a study to be conducted that examine the issue in this context. In this case, this study attempted to fill this gap by exploring the case of Indonesia. This research aimed to develop a model of IT innovation implementation in the context of HEIs in Indonesia. This study focused on post-adoption stage of IT innovation diffusion, which means that the IT innovation has been adopted by the organizations and it was implemented through the implementation process. The study examined the factors that contributed to the success of IT innovation implementation. The study also measured the significant relationships between IT implementation effectiveness and IT innovation effectiveness. The proposed model has been validated using a quantitative approach, specifically using the survey technique. The target population of this study is HEIs that have joined APTIKOM – the association of colleges and university that provide the ICT program and education in Indonesia. The 171 valid responses among 91 HEIs in the sample were then analysed using PLS-SEM techniques to generate and test the measurement and structural models. The results of this study highlighted that, in regard to factors contributing IT innovation implementation, learning orientation, implementation climate, implementation policies and practices, and top management support were considered as imperative variables on IT innovation implementation. The model developed based on this study contributed towards the knowledge domain on IT innovation implementation in the context of higher education. Practically, the findings contributed towards guiding HEI management in implementing IT innovation at their respective organization. Although the results were directly related to the Indonesia context, the management of HEIs in other developing countries may benefit indirectly from this study.